P‐127: Multi‐touch Tactile Display with Segmented Electrode Structure and Driving Method for Presenting Tactile Free‐shape Localized Textures. Issue 1 (25th September 2020) - Takeuchi, Shin; Haga, Hiroshi; Asai, Takuya; Sasaki, Harue; Shigemura, Koji
Abstract : We propose an electrostatic multi‐touch tactile display with a segmented electrode structure and electrode‐driving method for presentation of free‐shaped localized textures. This display solves the tactile crosstalk issue of our previously proposed tactile display. We evaluated the proposed display in a user test.